Середовищні музеї як засіб музеєфікації містобудівної спадщини - Ремешило-Рибчинська, О. І.; Брич, М. Т. (Видавництво Львівської політехніки, 2016)
Проаналізовано проблеми охорони історико-культурних пам’яток містобудівної спадщини, їх поєднання з регіоном, суспільством і оточенням. Запропоновано метод збереження пам’яток шляхом музеєфікації і створення на їх основі середовищних музеїв з метою максимального збереження та виявлення їхньої історико-культурної, наукової, художньої цінності. Здійснено спробу класифікації середовищних музеїв. In this article problems of historical and cultural monuments and urban planning heritage protection, their connection with the region, society and environment are analysed. The method of their preservation by way of museumfication and creation of environmental museums on their basis with the aim of preserving and revealing their historical, cultural, scientific and artistic value is proposed. The author attempts to classify environmental museums. Due to the rapid changes in the modern world, the acute question of monument conservation arises. Using historical and cultural heritage is the object of attention of the international community, and conservation is one of the most important factors in the harmonious development of society, all its systems and subsystems. The need to preserve cultural heritage of humanity entails the intensification of modern museum functioning. Museums now refer to new forms of urban heritage conservation. The proposed research is devoted to the environmental museums, where attractions of urban development, most revealing elements of culture, are the main exhibits. Since the architecture is directly linked with the complex synthesis of culture and customs, the monument should not be shown by themselves, but in combination with other related works of material and spiritual culture. Such complexes and ensembles are impossible to perceive, taking each individual object. It is important to consider them in the context of their original appearance and existence. The whole region, where there are several nearby monuments of architecture or town planning, needed to be seen as the holistic museum. Today the trend is a combination of architectural, archaeological and landscape monuments within the protected zones. This means a shift from preservation of individual monuments to museumfication of entire urban complexes, restoration of cultural and historical environment of the past. It is much easier and more efficient to create historical, cultural and architectural reservation, organize museum-reserves based on monuments of architectural and urban planning. The number of newly established environmental museums significantly surpasses the number of traditional museums. Undoubtedly, in the next decade, this tendency will only increase. Creating environmental museums today is an effective means of preserving the material and spiritual values, which helps to represent cultural heritage to the public and properly interpret it. The environmental museum today is the best form to store different types of historical and cultural heritage of architectural and urban planning, as well as to attempt to classify museumficated objects, most of which are very different types of environmental museums. Unfortunately, the current socio-cultural situation in Ukraine is not conducive to the development of the museum network. The problem of inclusion of fallen monuments of architecture and urban planning to modern life remains unresolved.
Environmental museum as means of urban planning heritage museumficationіі. Architecture of buildings and structures
Keywords: музеєфікація; містобудівна спадщина; середовищний музей; збереження пам’яток; museumfication; urban planning heritage; environmental museum; preservation of monuments; 72.025:069.4